2021
DOI: 10.1051/0004-6361/202141620
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reconnection and the Kelvin-Helmholtz instability in the solar corona

Abstract: Context. The magnetic Kelvin-Helmholtz instability (KHI) has been proposed as a means of generating magnetohydrodynamic turbulence and encouraging wave energy dissipation in the solar corona, particularly within transversely oscillating loops. Aims. Our goal is to determine whether the KHI encourages magnetic reconnection in oscillating flux tubes in the solar corona. This will establish whether the instability enhances the dissipation rate of energy stored in the magnetic field. Methods. We conducted a series… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…We can clearly see that the loop boundary is fully turbulent and extremely fine structures in vorticity have already been generated. Several authors have studied the evolution of vorticity in numerical simulations where the kink mode is excited (see, e.g., Terradas et al 2008;Antolin et al 2015;Howson et al 2017b;Karampelas et al 2017;Karampelas & Van Doorsselaere 2018;Guo et al 2019;Howson et al 2020Howson et al , 2021 and some of their results are comparable with the present ones. Similar vorticity structures as those displayed in Fig.…”
Section: Revisiting the Straight Magnetic Field Casesupporting
confidence: 78%
“…We can clearly see that the loop boundary is fully turbulent and extremely fine structures in vorticity have already been generated. Several authors have studied the evolution of vorticity in numerical simulations where the kink mode is excited (see, e.g., Terradas et al 2008;Antolin et al 2015;Howson et al 2017b;Karampelas et al 2017;Karampelas & Van Doorsselaere 2018;Guo et al 2019;Howson et al 2020Howson et al , 2021 and some of their results are comparable with the present ones. Similar vorticity structures as those displayed in Fig.…”
Section: Revisiting the Straight Magnetic Field Casesupporting
confidence: 78%
“…The results from the observations and simulations have suggested that the KHI and RTI vortices can twist and deform the magnetic field as well as change the local magnetic pressure, and a myriad of current sheets and vortices are produced through a turbulent cascade. It is also likely that magnetic reconnection is enhanced in the solar corona due to such wave processes (Howson et al 2021). However, it is unclear whether this sort of reconnection is only gradual and confined to the smallest turbulent scales, hence, not affecting the overall topology of the loop.…”
Section: Introductionmentioning
confidence: 99%
“…This process has been well studied in both analytical (e.g., Zaqarashvili et al 2015;Barbulescu et al 2019;Van Doorsselaere et al 2021) and numerical settings (e.g., Antolin et al 2014Antolin et al , 2015Antolin et al , 2018Magyar & Van Doorsselaere 2016;Karampelas & Van Doorsselaere 2018;Afanasyev et al 2019;Antolin & Van Doorsselaere 2019). The small spatial scales that form and the misalignment of magnetic field lines at the boundaries of Kelvin-Helmholtz vortices can drive plasma heating (Karampelas et al 2017) and lead to magnetic reconnection (Howson et al 2021). Due to the nature of the fundamental standing waves (perturbed velocities/ magnetic field largest at apex/footpoints), small scales in the velocity field tend to generate viscous heating at the loop apex, while small scales in the magnetic field typically produce ohmic heating at the loop footpoints (e.g., Karampelas et al 2017).…”
Section: Introductionmentioning
confidence: 99%